(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the prevalence of hepatic dysfunction and it’s clinical and biochemical spectrum in children presenting with dengue fever. Study Design: A prospective cross-sectional study Place and Duration of Study: This study was conducted at the Khairpur, Medical College and Teaching Hospital, from June 2017 to June 2020. Materials and Methods: Liver function of the patientswas assessed clinically as well as biochemically. Results: Hepatic dysfunction was observed 27.5% of patients. 58% were males and 42% were females. 69.5%, 25.2% and 07% had DF (Dengue fever), DHF (Dengue hemorrhagic fever) and DSS (Dengue shock syndrome) with increasing severity of hepatic involvement. Conclusion: Dengue fever can manifest with hepatic involvement. Children presenting with jaundice, hepatomegaly and elevated transaminases should raise the possibility of dengue infection and its severity.